P640 Neonatal arrhythmias: a 20 cases study. (June 2019) - Charfi, Manel; Hamad, Amel Ben; Loukil, Mouna; Regaieg, Chiraz; Bouraoui, Amira; Regaieg, Ridha; Hmida, Nedia; Abid, Dorra; Kammoun, Samir; Thabet, Afef Ben; Gargouri, Abdellatif
Abstract : Introduction: Arrhythmias in neonates are rare with an incidence reported to be 1 to 5%. Their diagnosis and treatment differs substantially from approaches used in an older child. Through this study we aim to identify epidemiology, clinical features, management and outcome of neonatal arrhythmias. Patients and methods: It's a retrospective study of all cases of arrhythmias hospitalized in the neonatal intensive care unit of Sfax between 2004 and 2018. Results: We registered 10 cases of congenital atrioventricular block (AVB), 8 cases of flutter and 2 cases of chaotic tachycardia. A male predominance was noted with a sex ratio of 2.3. Prenatal diagnosis was performed in 5 cases of atrial flutter by fetal echocardiography which was indicated because of fetal anasarca in 3 cases, a dilatation of the right heart cavities in one case and a fetal tachycardia in one case. Prenatal treatment was administered in 4 cases of atrial flutter. It was based on amiodarone in one case, digoxin in two cases and digoxin associated with sotalol then relayed by flecainide in one case. Ten newborns presented signs of heart failure. For the others, the clinical manifestation was an anomaly of the heart rhythm (bradycardia or tachycardia). Diagnosis was confirmed in all cases by electrocardiogram. Echocardiography was performed for all patients. It showed tight pulmonary narrowing in a case of flutter and transient myocarditis associated to an AVB in one case. After birth, an external electric conversion was necessary in 4 cases of atrial flutter and a pacemaker implantation was indicated in 5 cases of AVB. In the other cases, the treatment was medical (amiodarone for tachycardia and Isoproterenol for AVB). Only 4 newborns with AVB died in the post operative course of the pace maker implantation. For all other newborns the evolution was favorable. Conclusion: Neonatal arrhythmias can be serious and life threatening. The prognosis depends on the prompt of diagnosis which can be challenging at this age. Management must be rapid and multidisciplinary. Hence we insist on the importance of prenatal diagnosis.